6 years review of teenage pregnancy and it’s maternal and fetal outcome in HUSM - Muhammad, Nadhilah Izni (2022)
OBJECTIVE: To determine the incidence of the teenage pregnancy, it sociodemographic issues and to determine the obstetric risks and complications of teenage pregnancy in HUSM from the year 2015 till 2020. STUDY METHOD: This retrospective cohort study involved all the teenage pregnancy patient that delivered in Hospital Universiti Sains Malaysia. The data for sociodemographic, obstetric risks and complications were collected from the patient notes. Data were analyzed using univariate analyses and Chi square test or Fisher exact test will be used for categorical independent variable and independent t-test or Mann Whitney U test will be used for numerical independent variable depending on normality of data to look for the obstetric and neonatal outcome and as well as sociodemographic. RESULTS: A total of 405 teenage pregnancy patient participated in this study. They are divided into 2 groups, young teenage pregnancy (n=71) and older teenage pregnancy (n=334). Young teenage pregnancy group are the group that equal or less than 16 years old, while older teenage group are older than 16 years old lesser than 20 years old. The prevalence of teenage pregnancy in HUSM is 1.01% and the mean incidence are 10 births out of 1000 women. The teenage pregnancy found to have low in education level where 88.9% had only attended secondary school and 8.9% did not have any education level compare to only 1.2% had attending college or university. The incidence of eclampsia in younger teenage group found to be higher (4.1%) compare to older teenage group (0.3%). However this is not significantly different between this two group. Post-partum hemorrhage found to be higher in younger teenage group (5.6%) compare to older teenage group(2.7%). Uncomplicated intrapartum outcome are more higher in older teenage pregnancy group(93.7%) compare to young teenage pregnancy group(91.5%). Complicated delivery such as retained placenta, meconium stained liquor, shoulder dystocia and obstetric anal sphincter injuries are found to be low in both teenage group. There is however no significant different in the incidence of Pre-eclampsia, PROM, anemia and adverse birth outcome. 89.7% of the teenager pregnancy are from Malay ethnicity(87.9%) and incidence of premarital conception(17.8%) and single mother(11.9%) are higher. CONCLUSION The younger teenage group have higher rate of successful at spontaneous delivery compare to older teenage group. Both groups have uncomplicated intrapartum outcome. There are no significant different in antenatal complications, mode of deliveries and birth outcome in both teenage pregnancy groups.